The Psychology of Authenticity. Issue 1 (March 2019) - Newman, George E.
Perceptions of authenticity (or, inauthenticity) have been shown to affect people's judgments and behavior across a wide variety of domains. However, there is still ambiguity about how the concept should be defined. This is attributable, at least in part, to a growing list of different "kinds of authenticity" with little discussion of the potential overlaps between them. The goal of this paper is to reduce these various notions of authenticity into a more manageable set of constructs. Building on the work of Newman and Smith (2016a), three broad kinds of authenticity are proposed: Historical, Categorical, and Values authenticity. Two studies then examine the extent to which people's conceptions of authenticity naturally segment into these three types. Specifically, Study 1 asks participants about the various ways in which they might assess authenticity, whereas Study 2 examines individual differences in sensitivity to different kinds of inauthenticity. The results from both studies indicate a striking degree of convergence in support of these three broad dimensions. Moreover, different populations appear to be differentially concerned about these various ways of evaluating authenticity. The implications of this framework for existing and future work in this area are discussed.